Development of STEM-Oriented E-Modules to Improve Science Literacy Ability of Elementary School Students - Rizka Oktarina; Yanti Fitria; Syafri Ahmad; Zelhendri Zen (Jurnal Penelitian Pendidikan IPA, 2023)
The goal of this project is to create an electronic module, or E-Module, for third grade elementary school kids that is designed using the Book Creator application and integrated with a STEM learning strategy. Development research, also referred to as Research and Development (R&D) employing the ADDIE paradigm, is this kind of study. The subjects of this study are instrument validators, expert validators (material experts, linguists and media experts) and students in class III SDN 07 Kampung Jawa II, students in class III SDN 04 Rawang and students in class III SDN 17 Kampung Baru. The research instrument consisted of validation sheets, questionnaires and test instruments. The data analysis technique used is validity analysis and practicality analysis. The results of the validity by media experts are 91, 68% with very valid qualifications. The results of the validity of the linguists are equal to 88.95% with valid qualifications. The results of the validity of the media experts are equal to 90.41% with very valid qualifications. The percentage of the teacher's score for product feasibility is 92.06%, which is included in the very practical category. The practicality test percentage of students is 90.31%, which is included in the very practical category. Thus, this research succeeded in producing a STEM-based E-module to improve the scientific literacy skills of elementary school students.